Associations between abnormal spontaneous neural activity and clinical variables, eye movements, and event-related potential indicators in major depressive disorder - Zhang, Qinqin; Li, Xiaoling; Yan, Haohao; Wang, Yun; Ou, Yangpan; Yu, Yang; Liang, Jiaquan; Liao, Hairong; Wu, Wanting; Mai, Xiancong; Xie, Guojun; Guo, Wenbin (Frontiers in Neuroscience, 2023)
This study aimed to investigate the correlations between abnormal spontaneous neural activity (fractional amplitude of low-frequency fluctuations, fALFF) and clinical variables, eye movements, and event-related potential indicators in patients with major depressive disorder (MDD). We recruited 42 patients with MDD and 42 healthy controls (HCs) and collected their clinical variables, eye movement, and event-related potential related indicators, and resting-state functional magnetic resonance imaging (rs-fMRI) data. The fALFF, support vector machine (SVM), and correlation analysis were used to analyze the data. The results of the study showed that the fALFF values of the sensorimotor network, including the right middle temporal gyrus, right cerebellar Crus2, left occipital gyrus, and left middle temporal gyrus, were significantly higher compared to HCs. Correlation analysis showed that the abnormal fALFF value of the right cerebellar Crus2 was inversely correlated with the active coping scores of the Simplified Coping Style Questionnaire in the patients, and the correlation was no longer significant after the Bonferroni correction. No correlation was observed between abnormal fALFF values and clinical symptoms, neuropsychological tests, eye movements, and event-related potential-related indicators in patients with MDD. Patients with MDD exhibited enhanced spontaneous neural activity in the sensorimotor network. No associations were found between abnormal spontaneous neural activity and clinical variables, eye movements, and event-related potential related indicators in MDD.